The Effect of Temperature and Air Velocity on Drying Kinetics of Pistachio Nuts during Roasting by using Hot Air Flow - A Dini (Ferdowsi University of Mashhad, 2017)
Introduction Pistachio nut is one of the most delicious and nutritious nuts in the world and it is being used as a saltedand roasted product or as an ingredient in snacks, ice cream, desserts, etc. The purpose of roasting is to promote flavour and texture changes in nuts that ultimately increase the overall palatability of the product.Roasting involves a number of physico-chemical changes, including heat exchange, chemical reactions and drying. Knowledge of desorption kinetics is essential to predict the behavior of the material during roasting process and to design roaster equipment.The main aim of this research was to evaluate suitable models for predicting moisture ratio, the effect of air temperature and velocity on the drying kinetics of pistachio nuts and obtain the effective diffusivity coefficient and activation energy in the drying process during the roasting of pistachio nuts. Materials and Methods Dried Ahmadaghaei pistachio nuts were supplied from Kashefan Kavir company (Doraj co.) in Rafsanjan. Pistachio nuts were soaked in 17% salt solution for 8 minute and roasting was investigated at air temperatures of 120,130, 145, 160 and 170 °C and air velocities of 0.6, 0.88, 1.3, 1.72 and 2 ms-1. Five semi-theoretical and two empirical kinetic models were fitted to drying experimental data using nonlinear regression analysis techniques in the Curve Expert 2.2 computer program. Results and Discussion Tow-way ANOVA indicated that temperature and hot air velocity significantly affected the drying process during roasting of shelled pistachio nuts. The higher roasting temperatures and air velocities resulted in the higher drying rates. During first 10 min of roasting at constant air velocity of 1.3 ms-1, 64.5%, 70.3%, 77.1%, 83.5%, 89.7% of the moisture were removed at roasting air temperatures of 120 °C, 130 °C, 145 °C, 160 °C, 170 °C, respectively. The high regression coefficients (R2>0.996) and low reduced chi-square (χ2), mean relative deviation modulus P (%) and Root Mean Square Error (RMSE) indicated that the Weibull models are suitable for predicting moisture ratio. Correlations of the Weibull model constants with the variables of temperature and velocity were determined. Additionally, effective diffusivity (Deff) determined by using Fick’s second law was varied from 4.418×10-09 to 2.648×10-08 m2s-1 over the temperature and air velocity ranges. The lowest and highest Deff values were found for samples roasted at temperature of 120°C with air velocity of 0.6 m s-1and temperature of 170°C with air velocity of 2 ms-1, respectively. Temperature dependence of the diffusivity coefficient was described by Arrhenius-type relationship. Also average activation energy was obtained 26.615 kJ mol-1. Conclusions The results of this study showed that temperature and hot air velocity significantly affect the drying kinetics during roasting of pistachio nuts.The effective diffusion coefficient determined in this study was more than the limits specified in food products drying at lower temperatures and there was direct relationship between temperature and hot air velocity with effective diffusion. Activation energy was obtained close to some agricultural products.